AIDS Vaccination Studies Using an Ex Vivo Feline Immunodeficiency Virus Model: Protection from an Intraclade Challenge Administered Systemically or Mucosally by an Attenuated Vaccine - Pistello, Mauro (American Society for Microbiology, 2003)
Feline immunodeficiency virus (FIV) infection of domestic cats represents a valuable system through which to investigate criteria for antilentiviral vaccines in a natural host species. Here, we examined whether vaccination with a strain of FIV attenuated as a result of prolonged growth in vitro could protect against a fully virulent, highly heterologous intraclade challenge. The results indicated that the vaccine virus produced a low-grade infection with no detectable pathological effects and afforded a long-lasting sterilizing immunity if the challenge was delivered intraperitoneally as cell-free virus but not against a cell-associated intravaginal challenge. In the latter case, however, the replication and pathological consequences of the challenge virus were markedly suppressed. Together with similar results obtained in rhesus monkey models, these findings should give impulse to the development of attenuated FIV vaccines to be tested in controlled studies in field cats. Field studies may provide answers to some of the existing safety concerns surrounding attenuated AIDS vaccines in humans.